THE STORY OF THE PROPHET YUSUF IN THE QUR'AN: JULIA KRISTEVA'S INTERTEXTUAL APPROACH - Purnama, Rizal Faturohman (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2021)
This article discusses the story of the Prophet Joseph in the Qur'an. As the story of the Qur'an and the Bible, the story of the Prophet Joseph is very important to find out the difference between the two. Therefore, the approach used is intertextual initiated by Julia Kristeva who seeks to compare the two. By using this approach. There are a lot of differences. In terms of the structure of the Qur'an many simplifications, so the principle of haplology becomes dominant in every fragment. The most fundamental difference between the two is in terms of the theme to be raised, the story of the Prophet Joseph in the Qur'an is themed around the teachings of tawhid, while in the Bible themed power. Keywords: Prophet Joseph, al-Qur'an, Intertextual Abstrak Artikel ini membahas tentang kisah Nabi Yusuf dalam al-Qur’an. Sebagai kisah yang termuat dalam al-Qur’an dan Alkitab, kisah Nabi Yusuf sangat penting untuk ditemukan letak perbedaan antara keduanya. Oleh karena itu, pendekatan yang digunakan adalah intertekstual yang digagas oleh Julia Kristeva yang berusaha untuk membandingkan keduanya. Dengan menggunakan pendekatan ini. Ditemukan banyak perbedaan. Dari segi struktur al-Qur’an banyak melakukan penyederhanaan, sehingga prinsip haplology menjadi dominan dalam setiap fragmen. Perbedaan yang paling mendasar antara keduanya adalah dari segi tema yang hendak dimunculkan, kisah Nabi Yusuf dalam al-Qur’an bertemakan ajaran tauhid, sedangkan dalam Alkitab bertema kekuasaan. Kata Kunci: Nabi Yusuf, al-Qur’an, Intertekstual